The PENGARUH RISIKO BISNIS, PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA - Astuti, Indriani Indah; Purnamasari, Keti (Jurnal Riset Terapan Akuntansi, 2024)
This study was conducted to examine the effect of business risk, profitability and liquidity on capital structure at pharmaceutical companies in BEI. The purpose of this study is to determine and analyze the presence or absence of the influence of business risk, profitability and liquidity to the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange in 2019 to 2023. The total sample of this study is 10 companies determined through purposive sampling. The data analysis uses panel data regression that was previously tested to determine the effect in the panel regression estimation model. Based on the results of the classical assumption test, the research data has met the conditions in the use of panel data regression. Model is estimated using Fixed Effect Model (FEM). The results show that business risk, profitability and liquidity significantly affect the capital structure. Business risk has no effect on capital structure, profitability has significant negative effect the capital structure, and liquidity has significant positive effect on capital structure. Keywords: Business Risk, Profitability, Liquidity, Capital Structure